Interactions between gut microbiota and cardiovascular drugs: effects on drug therapeutic effect and side effect - Wang, Tianyu; Lan, Qingsu; Deng, Haonan; Han, Wenqiang; Zhang, Runtian; Zhong, Jingquan (Frontiers in Cardiovascular Medicine, 2025)
There exists a complex relationship between gut microbiota and cardiovascular diseases (CVD). On one hand, the plasma levels of various metabolites produced by gut microbiota, such as trimethylamine n-oxide (TMAO), short-chain fatty acid (SFCA), bile acid (BA), are closely related to the occurrence and development of CVD. On the other hand, CVD can affect gut microbiota, leading to gut microbiota dysbiosis or metabolic changes. Cardiovascular drugs are the cornerstone of treating CVD, especially oral medications that play an indispensable role in the long-term treatment of chronic CVD. Increasing research suggests that drugs entering the gastrointestinal environment interact with gut microbiota. Due to the individual differences in gut microbiota, the exploration of its mechanisms is insufficient. Therefore, the purpose of this review is to summarize the interactions between various common cardiovascular drugs and gut microbiota, and to highlight the impact of the gut microbiota on the therapeutical effects and side effects of cardiovascular drugs.